1991
DOI: 10.1116/1.577157
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen induced adhesion degradation at metal/polyimide interface

Abstract: The role of oxygen in affecting the adhesive bonding at the metal/polyimide (polyimide-on-metal) interface has been studied. Both pyromellitic dianhydride (PMDA) -oxydianiline (ODA) and biphenyl-tetracarboxylic dianhydride(BPDA) -p-phenylene diamine (PDA) based poly(amic acid) precursors were cast and fully imidized on metal surfaces of Cr, Cu, Ni, Co, Cu/Ni, and Cu/Co in a nitrogen atmosphere. The peel strengths at the polyimide-on-metal interface were measured, using a 90° peel test, immediately after curing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…At 600 • C, it appears that the thermal degradation of the PI matrix expedited the vertical migration of materials from the metal film and led to eventual coarsening of the particles in the vertical dimension. It was previously shown that using FT-IR, the PI film did quickly deteriorate above 500 • C in the presence of a metal film [10]. We also confirmed that the PI structure was in fact thermally damaged above 500 • C, using FT-IR measurements.…”
Section: Shown Insupporting
confidence: 88%
“…At 600 • C, it appears that the thermal degradation of the PI matrix expedited the vertical migration of materials from the metal film and led to eventual coarsening of the particles in the vertical dimension. It was previously shown that using FT-IR, the PI film did quickly deteriorate above 500 • C in the presence of a metal film [10]. We also confirmed that the PI structure was in fact thermally damaged above 500 • C, using FT-IR measurements.…”
Section: Shown Insupporting
confidence: 88%
“…17 Shin et al reported that the loss of adhesion of polyimide to Cu is due to the metal-catalyzed thermal oxidative degradation of the polyimide at the metal/ polyimide interface, while that for Cr and Ni it is due to oxidation-induced debonding at the metal/polyimide interfaces. 18 As a result, in this study, the XPS and AFM results identified that the FCCL with the higher Cr ratio experienced a smaller change of the chemical functions and fracture surface roughness than did the FCCL with the lower Cr ratio.…”
Section: Resultsmentioning
confidence: 89%
“…Cu may also act as a catalyst to decompose polymeric bonds under oxygen or a moisture containing environment at elevated temperatures. 8) In order to improve the interface adhesion strength, an additional metal layer is generally deposited at the Cu/PI interface. Chromium (Cr) has been used as an interface metal layer because of the formation of strong Cr-C bonds.…”
Section: Introductionmentioning
confidence: 99%